A comparison of CO2 dynamics and air‐water fluxes in a river‐dominated estuary and a mangrove‐dominated marine estuary. Issue 22 (17th November 2016) - Akhand, Anirban; Chanda, Abhra; Manna, Sudip; Das, Sourav; Hazra, Sugata; Roy, Rajdeep; Choudhury, S. B.; Rao, K. H.; Dadhwal, V. K.; Chakraborty, Kunal; Mostofa, K. M. G.; Tokoro, T.; et al.
Abstract: The fugacity of CO2 ( f CO2 (water)) and air‐water CO2 flux were compared between a river‐dominated anthropogenically disturbed open estuary, the Hugli, and a comparatively pristine mangrove‐dominated semiclosed marine estuary, the Matla, on the east coast of India. Annual mean salinity of the Hugli Estuary (≈7.1) was much less compared to the Matla Estuary (≈20.0). All the stations of the Hugli Estuary were highly supersaturated with CO2 (annual mean ~ 2200 µatm), whereas the Matla was marginally oversaturated (annual mean ~ 530 µatm). During the postmonsoon season, the outer station of the Matla Estuary was under saturated with respect to CO2 and acted as a sink. The annual mean CO2 emission from the Hugli Estuary (32.4 mol C m −2  yr −1 ) was 14 times higher than the Matla Estuary (2.3 mol C m −2  yr −1 ). CO2 efflux rate from the Hugli Estuary has increased drastically in the last decade, which is attributed to increased runoff from the river‐dominated estuary. Key Points: River‐dominated Hugli Estuary emits 14 times more CO2 than the marine‐dominated Matla Estuary In the last 14 years the CO2 efflux rate from the Hugli Estuary has increased more than twofold The f CO2 (water) value of the Matla, a mangrove estuary, is at the lower end of the reported data from other mangrove ecosystems of the world